A public health approach for deciding policy on infant feeding and mother–infant contact in the context of COVID-19. Issue 4 (April 2021) - Rollins, Nigel; Minckas, Nicole; Jehan, Fyezah; Lodha, Rakesh; Raiten, Daniel; Thorne, Claire; Van de Perre, Philippe; Ververs, Mija; Walker, Neff; Bahl, Rajiv; Victora, Cesar G; ,
Summary: The COVID-19 pandemic has raised concern about the possibility and effects of mother–infant transmission of SARS-CoV-2 through breastfeeding and close contact. The insufficient available evidence has resulted in differing recommendations by health professional associations and national health authorities. We present an approach for deciding public health policy on infant feeding and mother–infant contact in the context of COVID-19, or for future emerging viruses, that balances the risks that are associated with viral infection against child survival, lifelong health, and development, and also maternal health. Using the Lives Saved Tool, we used available data to show how different public health approaches might affect infant mortality. Based on existing evidence, including population and survival estimates, the number of infant deaths in low-income and middle-income countries due to COVID-19 (2020–21) might range between 1800 and 2800. By contrast, if mothers with confirmed SARS-CoV-2 infection are recommended to separate from their newborn babies and avoid or stop breastfeeding, additional deaths among infants would range between 188 000 and 273 000.